CONCEPT MAPPING APPLICATION FOR NURSING CARE IN MATERNITY STAGE - WITRI HASTUTI (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Background: Critical thinking concept is the important element in order delivery a quality nursing care.  Learning process is designed using effective learning method to support critical thinking for students in the clinical practice environment. Concept mapping is a tool to enhance critical thinking for students by making connection between prior knowledge  with new information in order to solve nursing problems. Objective: to know the effect concept mapping application in clinical learning towards quality of nursing documentation by nursing students in Profesi Ners level Karya Husada Semarang Health Science College who have clinical practice in maternity. Methode: Using quantitative research with only posttest design, with sampel were 30 nursing students in Profesi Ners level using total sampling. Data Analysis used Mann-whitney. Result: Intervention group had average grade higher was 22,90 than control grou was 8,10. Conclusion: There was effect of concept mapping in order delivery maternity nursing care for nursing students in Profesi  Ners level. Key words: Concept mapping, Maternity nursing care